2018
DOI: 10.1186/s13071-018-2790-z
|View full text |Cite
|
Sign up to set email alerts
|

First identification and multilocus genotyping of Giardia duodenalis in pet chipmunks (Eutamias asiaticus) in Sichuan Province, southwestern China

Abstract: BackgroundGiardia duodenalis is a flagellated parasite that causes diarrhea in humans and other animals. Although G. duodenalis is found in companion animals worldwide, information regarding the prevalence and genetic characteristics of G. duodenalis in pet chipmunks in China is limited. The present study therefore aimed to investigate the prevalence and genotypes of G. duodenalis in pet chipmunks in Sichuan province, southwestern China, as well as to assess zoonotic potential of revealed assemblages.ResultsA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…To address this point, a large number of epidemiological investigations should be implemented in future studies. However, assemblage B could be transmitted zoonotically [ 70 – 72 ] and has a broad host range, including livestock, companion animals, fish, and marine and wild mammals [ 12 , 13 , 18 , 21 , 26 , 73 , 74 ]. Furthermore, assemblage B was also detected in some water bodies [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this point, a large number of epidemiological investigations should be implemented in future studies. However, assemblage B could be transmitted zoonotically [ 70 – 72 ] and has a broad host range, including livestock, companion animals, fish, and marine and wild mammals [ 12 , 13 , 18 , 21 , 26 , 73 , 74 ]. Furthermore, assemblage B was also detected in some water bodies [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although the prevalence of G. duodenalis in bamboo rats was, until now, unknown, the presence of this parasite in other rodents (e.g. rats, mice, rabbits, chipmunks, chinchillas, guinea pigs, beavers) has been reported in China, Romania, Laos, America, Germany, Austria, Denmark, Hungary, Finland, France, Italy, Luxembourg, the Netherlands, Norway, Poland, Portugal and Sweden, with a prevalence of 1.9–83.0% [ 9 , 13 , 14 , 36 , 38 42 ]. Among them, high prevalence was detected in chinchillas (55.7%) from Romania [ 14 ], chinchillas (61.4%) from European countries [ 42 ] and mice (83%) from Germany [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…in these animal hosts has been published [ 6 , 7 , 15 , 16 ]. Reports have demonstrated that G. duodenalis infections in rodents in Australia, Belgium, China, Croatia, Germany, Malaysia, Poland, Romania, Spain, Sweden, and the USA ( Table 4 ) have prevalence rates ranging from 1.2% to 100% [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Herein, molecular analysis of 308 fecal samples collected from coypus in six provinces in China confirmed a G. duodenalis prevalence of 12.3% (38/308).…”
Section: Discussionmentioning
confidence: 99%
“…have been detected in rodents, including G. muris and G. microti [ 20 , 35 ]. To date, in China, G. duodenalis has been reported in rodents of several genera, including Chinchillas ( Chinchilla lanigera ), Asian house rats ( Rattus tanezumi ), brown rats ( Rattus norvegicus ), house mice ( Mus musculus ), chipmunks ( Eutamias asiaticus ), and bamboo rats ( Rhizomys sinensis ) [ 18 , 19 , 26 , 30 ]. In previous work, seven assemblages of G. duodenalis were found in rodents, including A, B, C, D, E, F, and G ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…China: house mouse (3.2%, 1/31); Asian house rat (6.1%, 2/33); brown rat (6.6%, 11/168 and 9.3%, 33/355); pet chipmunks (8.6%, 24/279); bamboo rat (10.8%, 52/480); coypus (12.3%, 38/308); pet chinchillas (27.1%, 38/140) [26,38,[54][55][56][57] (Table 3).…”
Section: Author Contributionsmentioning
confidence: 99%